A Systematic Review and Meta-analysis Does Kangaroo Mother Care (KMC) Reduce The Duration of Phototherapy in Infants with Jaundice - เอกสมัย สุวลักษณ์; อารยะธนิตกุล บุศย์รินทร์; ศรีปะโค พิชญากร; ล้ำตระกูล สุอารี (Journal of The Royal Thai Army Nurses, 2019)
Approximately 50 percent of infants were diagnosed neonatal jaundice after birth, which phototherapy is an important method to reduce the bilirubin level. However, side effects of phototherapy, for example, baby bronze syndrome and childhood asthma could endanger those infants. Therefore, reducing the duration of phototherapy could be advantageous for them. Also, some researchers found applying Kangaroo Mother Care (KMC) in newborns receiving phototherapy could shorten the phototherapy period. The purpose of this study is to assess the available evidence comparing the duration of phototherapy when applying KMC in infants during receiving phototherapy. For this review, the Cochrane approach was used to report. The studies were retrieved from four databases: MEDLINE, EMBASE, CINAHL, and CENTRAL between 10 and 18 March 2018. The Cochrane Collaboration’s tool were applied to assess the risk of bias through all studies. Moreover, the meta-analysis was used for synthesizing the data. The results were two RCTs studies which a total of 322 infants were included in the analysis part. The finding found that applying KMC could reduce the duration pf phototherapy in infants with jaundice. n conclusion, even the finding shows the application of KMC can reduce the duration of phototherapy in infants with jaundice, the level of the evidence is very low because the high risk of bias of both papers. However, there is no disadvantages from applying KMC. Therefore, using KMC during receiving phototherapy is strongly recommended with the low quality of the evidence. Furthermore, rigorous RCTs studies with generate the high quality evidence for this article are required.